2013
DOI: 10.13102/sociobiology.v60i2.150-153
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Hydramethylnon to Leaf-cutting Ant Atta sexdens rubropilosa Forel (Hymenoptera: Formicidae)

Abstract: Since 2009, when sulfluramid was listed in annex B of the Stockholm Convention’s Persistent Organic Pollutants, effort has been made to search for other active ingredients to use in baits for controlling leaf-cutting ants in Brazil. Considering that active ingredients that inhibit insect cellular respiration have been shown to be effective in controlling ants, the current work aimed at assessing the toxicity of hydramethylnon to Atta sexdens rubropilosa workers. Hydramethylnon was dissolved in acetone and in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 11 publications
(7 reference statements)
1
28
1
4
Order By: Relevance
“…Sesamin exerted a fungicidal effect at a concentration of 70µg.ml -1 (Bueno et al, 2004). This result disagrees with the findings of Ribeiro et al (1998) who demonstrated complete inhibition of the fungus at a low concentration (2.5µg.ml -1 ).…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Sesamin exerted a fungicidal effect at a concentration of 70µg.ml -1 (Bueno et al, 2004). This result disagrees with the findings of Ribeiro et al (1998) who demonstrated complete inhibition of the fungus at a low concentration (2.5µg.ml -1 ).…”
Section: Discussioncontrasting
confidence: 88%
“…Leaf-cutting ants of the genera Atta and Acromyrmex (Hymenoptera: Formicidae) cultivate a symbiotic fungus, Bigi et al, 1998;Kitamura et al, 1999;Bigi et al, 2004;Caffarini et al, 2008;Alonso & Santos, 2013), Sesamum (Hebling et al, 1991;Bueno et al, 1995;Ribeiro et al, 1998;Peres Filho et al, 2003;Morini et al, 2005;Bueno et al, 2004), Canavalia ensiformis (Hebling et al, 2000;Rodriguez et al, 2008;Valderrama-Eslava et al, 2009;Aubad-Lopez, 2011;Varon et al 2007), Tithonia diversifolia (Giraldo-Echeverri, 2005;Castano, 2009) and Azidarachta indica (Bigi et al, 2004;Gruber & Valdix, 2003;Herrera, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Pesquisas sobre plantas tóxicas, visando a extração e identificação do material tóxico às formigas ou a seu fungo têm sido realizadas. O uso de substâncias tóxicas, extraídas de vegetais, poderá apresentar-se, no futuro, como possibilidade de controle (Hebling et al, 2000;Bueno et al, 2004;Valderrama-Eslava et al, 2009).…”
Section: Controle De Formigas Cortadeirasunclassified
“…A saber, diversos trabalhos evidenciam a eficiência de espécies vegetais no controle de formigas cortadeiras ou do fungo simbionte sendo: Aristolochia trilobata (Aristolochiaceae) (OLIVEIRA et al, 2017); Ateleia glazioviana (Fabaceae) (CANTARELLI et al, 2005); Canavalia ensiformis (Fabaceae) (HEBLING et al, 2000a); Cipadessa fruticosa (Meliaceae) (LEITE et al, 2005); Eplingiella fruticosa (Lamiaceae) (SILVA, 2017) Eugenia florida e Eugenia handroana (Myrtaceae) (TORRES et al, 2014); Ipomoea batatas (Convolvulaceae) (HEBLING et al, 2000b); Ricinus communis (Euphorbiaceae) (ACÁCIO-BIGI et al, 2004); Simarouba versicolor (Simaroubaceae) (PEÑAFLOR et al, 2009); Sesamum indicum (Pedaliaceae) (RIBEIRO et al, 1998;BUENO et al, 2004;MORINI et al, 2005), Trichilia pallida (Meliaceae) e Zanthoxylum pohlianum (Rutaceae) (TORRES et al, 2014); Melaleuca alternifólia (Myrtaceae) (BUTELERA et al, 2019); Simarouba amara (Simaroubaceae) e Zanthoxylum rhoifolium (Rutaceae) (GOMES, 2016); Sesamum indicum (Pedaliaceae) (RIBEIRO et al, 1998;BUENO et al, 2004;MORINI et al, 2005;ARAÚJO, 2016).…”
Section: Iscas Biológicas E Plantas Repelentesunclassified